CUSTOMS OF THE REPUBLIC OF UZBEKISTAN SYSTEM DEVELOPMENT STATUS (Academicia Globe: Inderscience Research, 2025)
The article examines the current state of the customs system of the Republic of Uzbekistan, and considers reforms in customs administration, work carried out on the development of the sector, work carried out on personnel training and advanced training, international cooperation, and prospects for the development of the sector.